Impacts of Drinking Water Project on Livelihood of Rural Women - Neupane, Bhim Prasad (Himalayan Journal of Sociology and Anthropology, 2011)
Based on the study of PUDWP (Pelakot Udiyachour Drinking Water Project) area of Syangja district the study construed that with access to water, there has been an increase in instances of animal rearing and kitchen gardening. It is saving time of the women due to the installation of tap water supply thus helping women to carry out other activities. For the women of the poor and poorest households, the time saved has helped them to include in livestock raising and agricultural activities and wage labour, thus, contributing to their household economy and women empowerment. DOI: http://dx.doi.org/10.3126/hjsa.v4i0.4665 Himalayan Journal of Sociology and Anthropology Vol.IV (2010) 15-27